IMPLEMENTASI APLIKASI TRACER STUDY BERBASIS WEBSITE DI SMK IHYA’ ULUMUDIN - Rohman, Abdur; Ayatullah, Mohamad Dimyati; Ratri, Indira Nuansa; Suardinata, I Wayan; Prasetyo, Junaedi (Universitas Nusantara PGRI Kediri, 2023)
Tracer study tracking of school alumni has an important role in improving and measuring the quality of education. Currently, Ihya Ulummudin Vocational School carries out tracer studies using manual methods with paper, resulting in limited and less than optimal information. Filling in this method is only able to track 20% of the number of graduates each year. This data must be reported to the Director General of Vocational Studies every year, but the school has difficulty providing this data information. To overcome this, the creation of a web-based tracer study application was carried out in discussion with the SMK. After the application is complete, testing and implementation of the application is carried out with graduating alumni. Workshops and training related to tracer studies were also held to support the use of this system. This application allows filling out questionnaires more quickly and accurately, as well as connecting alumni with the latest information regarding their careers. The results of this service show that the increase in tracer study filling has increased to above 90% and almost 80% of respondents expressed satisfaction with this application. With the website-based tracer study application that has been implemented, it will make it easier for managers to collect data on alumni of SMK Ihya Ulumuddin effectively and efficiently every year, as well as answer tracer study questions more accurately.